Solvatochromism and Cis-Trans Isomerism in Azobenzene-4-Sulfonyl Chloride - Sidir, İsa; Sidir, Yadigar Gülseven; Berber, Halil; FAUSTO, RUI (Springer Nature, 2025)
Solvatochromism exhibited by azobenzene-4-sulfonyl chloride (here abbreviated as Azo-SCl) has been investigated in a series of non-polar, polar-aprotic and polar-protic solvents. The UV-vis spectra of Azo-SCl exhibit two long-wavelength bands, observed at 321-330 nm (band-I) and 435-461 nm (band-II), which are ascribed to the pi*-pi (S2 <- S0) and pi*-n (S1 <- S0) transitions, respectively. The shorter wavelength band indicates a reversal in solvatochromism, from negative to positive solvatochromism, for a solvent with a dielectric constant of 32.66 (which is characteristic of methanol), while the longer wavelength band signposts negative solvatochromism in all range of solvent's dielectric constant investigated, demonstrating different interactions with the solvents in the S2 and S1 excited states. Using Catal & aacute;n and Kamlet-Taft solvation energy models, we found that the shift in the solvatochromic behavior of band-I (S2 <- S0) happens because solvent dipolarity/polarizability and hydrogen bonding affect the S2 state in opposite ways. Dipolarity/polarizability stabilizes the S2 state compared to the ground state, while hydrogen bonding destabilizes it. In contrast, for S1, both effects work together to destabilize the excited state. For all studied solvents, UV irradiation (lambda >= 311 nm; room temperature) was found to lead to fast trans-cis azo photoisomerization. In the absence of light, the photogenerated cis form quickly converts back to the trans form. Interpretation of the experimental data is supported by quantum chemical calculations undertaken within the Density Functional Theory (DFT) framework, including Time Dependent DFT calculations for excited states.
Keywords: Azo dye; Photochemistry; Photoisomerization; Reversal in solvatochromism; Solvent effects; UV irradiation